Heterologous fibrin biopolymer associated to a single suture stitch enables the return of neuromuscular junction to its mature pattern after peripheral nerve injury - Pinto, Carina Guidi [UNESP] (2021)
Denervation leads to severe atrophy of neuromuscular junction (NMJ) structure including decrease of the expression of fundamental proteins. Up to now, conventional suture has been the gold standard method used to correct this injury. Fibrin sealant is one of the alternatives proposed to optimize this method. This study verified if the association of fibrin sealant - Heterologous Fibrin Biopolymer (HFB) and a single suture stitch promotes return of morphology and NMJ structure to mature pattern after peripheral nerve injury. Forty Wistar rats were distributed into 4 groups: Sham-Control (SC), Denervated-Control (DC), Suture-Lesion (SL) and Suture-Lesion + HFB (SFS). In SC group only the right sciatic nerve identification was done. In DC, SL and SFS groups fixation of nerve stumps on musculature immediately after neurotmesis was performed. After seven days, stump reconnection with 3 stitches in SL and a single stitch associated with HFB in SFS were done. After sixty days right soleus muscles were prepared for nicotinic acetylcholine receptors (nAChRs) and nerve terminal confocal analyses, and for nAChRs (α1, ε e γ), S100, Agrin, LRP-4, MMP-3, Rapsyn western blotting analyses. SC group presented normal morphology. In DC group it was observed flattening of NMJ, fragmentation of nAChRs and tangled nerve terminals. The majority of the parameters of SL and SFS groups presented values in between SC and DC groups. There was an increase of relative planar area in these groups (SL and SFS) highlighting that there was less nAChRs fragmentation and the values of protein expression showed return of nAChRs to mature pattern. Use of HFB associated with a single suture stitch decreased surgical time, minimized suture injuries, did not alter nerve regeneration and presented potential to reestablish the NMJ apparatus. These consolidated results encourage surgeons to develop future clinical trials to install definitively this new approach both for reconstructive surgery and neurosurgery.